Multiple view geometry in computer vision - Hartley, Richard (Cambridge University Press, 2003)
Introduces the geometric foundations of multiple-view analysis in computer vision, covering camera models, epipolar geometry, 3D reconstruction, motion estimation, and robust computational methods used in vision algorithms.